DEGREE I IRON DEFICIENCY ANEMIA IN CHILDREN OF UZBEKISTAN - Asrorov Akmal Aminjonovich (Journal Park Publishing, 2025)
This article studied patients with IDA, determined the mild degree of the disease in children and highlighted the general condition of the examined patients. It is explained that it causes anemia, gastrointestinal tract problems, rickets, and frequent colds.
Keywords: IDA, starch, Asthenoneurotic syndrome, rickets, ARVI, lethargy, asthenia, apathy.